Prevalence of Reported Temporomandibular Disorders in Children and Adolescents: Systematic Review and Meta-Analysis - Ana Alvear Miquilena; Robert Velepucha Torres; Luis Chauca-Bajaña; Mayra Carrera Trejo; Susana Loayza Lara; Alba Pérez-Jardón; Juan Suarez-Palacios; Byron Velásquez Ron (Applied Sciences, 2024)
The prevalence of temporomandibular disorders during childhood and adolescence reported until 2019 was between 7 and 68%. The aim of the present study is to determine the prevalence of temporomandibular disorders in children. This study, registered in The International Prospective Register of Systematic Reviews (CRD42022378908), assessed the prevalence of temporomandibular disorders in children and adolescents through the Research Diagnostic Criteria for Temporomandibular Disorders. Information was restricted based on the age and language of publication. In total, 985 records were identified through databases (EBSCO, PubMed, Web of Science, Scopus, and Cochrane Library) and 45 through grey literature sources (SciELO, Google Scholar, and Latindex). After removing duplicates and irrelevant records, 285 studies were screened, of which 32 had their full text assessed. Eight were included for qualitative and quantitative synthesis. The prevalence of muscle pain ranged from 0% to 31%; arthralgia ranged from 0.8% to 3.5%; disc displacement with reduction ranged from 0.4% to 14.4%; disc displacement without reduction ranged from 0% to 0.3%; osteoarthritis ranged from 0% to 0.6%; and osteoarthritis (in another context) ranged from 0% to 2.2%. This review highlights the varying prevalence of temporomandibular disorders (TMDs) in children and adolescents, with muscle pain as the most common symptom. Despite advancements in diagnostic criteria, gaps in imaging and psychological evaluation persist.